The English Teacher’s Written Corrective Feedback on the Students’ Writings in Vocational High School - Firyaal Mujahidah; Made Adi Andayani T.; Siti Sundari (English Education Study Program, 2021)
This study was aimed to find out the types of Written Corrective Feedback (WCF) given by the English teacher to the students’ writings, the reason of the teacher in giving certain types of WCF, and the contributions of the WCF for the students. This study employed a case study design which involved one English teacher and three students from different acquisition levels. The data were obtained from documentation and interview. The types of WCF given by the teacher were classified by using the theory from Ellis (2008). The data from the interview were analyzed by using thematic analysis proposed by Braun and Clarke (2006). The results showed that the teacher used Direct WCF, Unfocused WCF, and Electronic Feedback in correcting the students’ errors. It was found that the teacher gave those types of WCF in order to make the students understand about the mistakes that they made in their writings. It was also found that high and medium achieving students stated that WCF from their teacher were beneficial for them in order to avoid the same mistakes in the future while low achieving student did not get the benefit of feedback.